Rethinking Teacher Professional Development in Public Secondary Schools in Zimbabwe - Mugwaze, Fortunate (Acitya: Journal of Teaching and Education, 2025)
Effective professional development practices are instrumental to the performance of schools as teachers play a pivotal role in shaping educational outcomes for learners in any country. In Zimbabwe, economic and social challenges have affected the availability, relevance, and effectiveness of professional development for teachers in public secondary schools. The principals' lack of instructional leadership and poor management skills have exacerbated the situation. Major gaps exist between current practices and strategic goals, highlighting the need for improved professional development. The study is motivated by the urgent need to rethink and redefine professional development in schools in Zimbabwe to improve teacher performance and retention. Situated in the interpretivism paradigm, this qualitative study used semi-structured interviews and document study to gather data. Findings highlight the urgent need for context-specific, continuous, and culturally responsive professional development programmes that address classroom management, discipline, and indigenous knowledge systems. Additionally, the study identifies the need for leadership training, enhanced support systems, and incentives for teacher engagement in professional development. The findings contribute to the broader discourse on human capital development in education, offering practical recommendations for improving professional development in resource-constrained and challenging environments.